Visible Spectral Atlas of Geostationary Satellites from Tucson, AZ for Differentiating Between Natural and Artificial Objects - Adam Battle; Vishnu Reddy; Roberto Furfaro; Tanner Campbell (The Planetary Science Journal)
As near-Earth object (NEO) surveys continue to search for smaller NEOs, they will also detect an increasing number of temporarily captured objects, or minimoons, in geocentric orbital space. Derelict spacecraft and debris in Earth orbit and cislunar space can be mistaken for minimoons, but spectral characterization can distinguish between the two categories of objects. However, systematic noncompositional effects due to nightly and seasonal phase angle changes on artificial objects need to be quantified before such distinctions can be made. These effects have been studied on small solar system bodies, but very little on artificial bodies. We present the reduced data of our multiyear visible wavelength (450–950 nm) spectral campaign of the geostationary Earth-orbiting (GEO) satellite belt from Tucson, AZ, and include comparisons to relevant planetary materials. Although some bus types have steeper spectral slopes than planetary materials, certain bus type spectral features can be confused for planetary materials. One example is a rollover at red wavelengths in the Eurostar-3000 bus-type spectrum that appears similar to mineralogical absorption bands on S- and L-type asteroids. Observations include a total of 96 unique GEO satellites across 192 separate nights from 2020 to 2022. A select subset of GEO satellites is repeatedly observed to measure seasonal variations. Our methods for data acquisition, processing, and cleaning are outlined in this paper. A summary of the atlas shows the full night median spectrum with phase variations and a lightcurve of brightness versus phase angle for each of the 284 sets of data collected.